Pentahelix Collaboration in the Recovery and Development of the Mekko Beach Tourism Sector Based on East Flores Regency Regional Regulation Article 12 Paragraph 2 Number 4 of 2015 From the Perspective of Siyasah Dusturiyah - Ismail Malik; Asro Asro; Taufiq Alamsyah (Journal Equity of Law and Governance, 2024)
The study examines the pentahelix collaboration model involving government, community, academia, business, and media in the tourism recovery and development of Mekko Beach, East Flores Regency. Despite its potential, the region faces challenges like limited infrastructure and promotional efforts. Based on Regional Regulation Article 12 Paragraph 2 Number 4 of 2015 from a siyasah dusturiyah perspective. The introduction explains the importance of the tourism sector for East Flores Regency and the challenges faced in developing Mekko Beach in a sustainable manner. The aim of the research is to analyze the role of each actor in pentahelix collaboration and the effectiveness of implementing regional regulations. The research method uses a qualitative descriptive approach with case studies, collecting data through interviews with stakeholders and document analysis. The findings highlight the importance of justice, public good, and transparency in effective collaboration. Although progress has been made, gaps remain between policy and practice, particularly in resource allocation and community participation. Strengthening coordination and enhancing local involvement are crucial for overcoming these challenges and achieving sustainable tourism development. Further research is suggested to explore innovative community engagement strategies in similar contexts.